Brain Informatics International Conference, BI 2010, Toronto, ON, Canada, August 28-30, 2010. Proceedings - Yao, Yiyu.; Sun, Ron.; Poggio, Tomaso.; Liu, Jiming.; Zhong, Ning.; Huang, Jimmy. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the International Conference on Brain Informatics, BI 2010, held in Toronto, China, in August 2010. The 60 revised full papers presented were carefully reviewed and selected from 222 submissions. The papers are organized in topical sections on cognitive computing; data brain and analysis; neuronal modeling and brain modeling; perception and information processing; learning; cognition-inspired applications; and WICI perspectives on brain informatics.